Two-mass vibrating conveyer with nonparallel flat springs - Koruniak, Petro; Nishchenko, Iryna; Shenbor, Vladyslav; Korendiy, Vitaliy (Publishing House of Lviv Polytechnic National University, 2016)
The analysis of operation of vibrating conveyers with nonparallel placement of flat springs is carried out. The motion of mechanical oscillating system is investigated. The structure of the supporting unit for flat springs fastening is propounded. This structure allows simplifying of setting-up of two-mass vibrating conveyers with the aim to ensure the effective operation. The models of conveyers with nonparallel placement of springs, providing the accurate calculations of rigidities and angles of flat springs inclinations, considerably simplify the structures of conveyers and their setting-up to ensure the prescribed angles of vibrations. The proposed structure of fastening of flat springs ends allows increasing of operation efficiency of the two-mass vibrating conveyer. Due to such setting-up of the equipment it is possible to compensate some of its theoretical and structural faults. On the basis of presented investigations, it is planned to develop the three-mass models of conveyers-separators with transporting of separated components in different directions.